PENGGUNAAN KLAUSULA BAKU DALAM PERJANJIAN E-COMMERCE DI TINJAU DARI PERSPEKTIF PERLINDUNGAN KONSUMEN - Fadel Edo Romires (Jurnal Inovasi Penelitian, 2022)
Abstract The rapid and advanced achievement of internet technology makes it easier to access any information needed, including product information. The existence of this convenience makes it a very important potential to be able to influence trading patterns, whether done online. The ability of these computers to be interconnected with one another opens up opportunities for the emergence of a new marketing method for commercial products, both in the form of goods and services. This method of marketing or buying and selling via the internet is known as electronic commerce (e-commerce). Currently, there is no definite definition of e-commerce that has been standardized and mutually agreed upon, but in the general sense accepted by the community, e-commerce is trade carried out via the internet. The existence of standard clauses as a medium to facilitate buying and selling transactions between producers and consumers turns out to be misused by producers by providing conditions that are very detrimental to consumers, including in banking credit agreements, insurance agreements, goods custody agreements, and buying and selling agreements through e-commerce. . One of the standard clauses reads "goods that have been purchased cannot be returned, damaged/lost goods are not our responsibility". The legal material analysis technique used is a normative analysis technique using logic or legal reasoning deductive methods, so that conclusions and prescriptives are obtained on the legal issues studied. So the validity of the standard clauses in e-commerce transactions is valid as long as it does not violate Article 1337 BW and Article 18 paragraphs 1 and 2 of the Consumer Protection Act. BPSK and LPKSM as non-government institutions that have the task of resolving disputes that arise between business actors and consumers in the author's view have not been able to provide maximum protection, and can file a lawsuit against the law based on Article 1364 of the Civil Code. With the intent and purpose can demand business actors to pay compensation experienced by consumers.